2004
DOI: 10.1002/marc.200400148
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approach of Evaluating Polymer Nanocomposite Structure by Measurements of the Freezing‐Point Depression

Abstract: IntroductionIn recent years, polymer/layered silicate (PLS) nanocomposites have attracted great interest, both in industry and in academia, because they exhibit unique properties not shared by their micro counterparts or conventional filled polymers. [1][2][3][4][5] The addition of just a few weight percent (<5 wt.-%) of nanolayered inorganic material gives rise to sensible increases in the stiffness and strength with minimal loss of ductility and impact resistance, [6,7] decreased gas permeability [8,9] and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…It has been reported that the freezing point of a solvent imbibed in the swollen vulcanizate would be declined . This could be because the rubber network restricts the nucleation process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the freezing point of a solvent imbibed in the swollen vulcanizate would be declined . This could be because the rubber network restricts the nucleation process.…”
Section: Resultsmentioning
confidence: 99%
“…This could be because the rubber network restricts the nucleation process. Thus, the depression degree of the freezing point can evaluate the interfacial interaction between filler and rubber . The freezing curves of the composites swollen in cyclohexane are recorded.…”
Section: Resultsmentioning
confidence: 99%
“…To confirm the limited interfacial crosslinking in CPT‐modified systems, freezing point depression for swollen samples was used to evaluate filler‐rubber interactions . Freezing point depression of the solvent in rubber composites was previously correlated to the interactions between filler and rubber by Valentín et al DSC curves of the samples are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…21 The formation of vacuoles was confirmed by cryoporosimetry measurements which have been already applied in the study of rubber network structure and polymer-filler interactions. 28,45 This procedure is based on the anomalous freezing point depression of solvent imbibed in elastomer compounds due to the restrictions caused by the mesh sizes in the nucleation process of the solvent. Two exothermic transitions related with the freezing temperature of the solvent (cyclohexane in this study) were observed (Fig.…”
Section: Silica-polymer Interfacementioning
confidence: 99%